Grundgestalt, multi-piece, and intertextuality in Brahams's opp. 117, 118, and 119 - Leigh, Martin (1998)
Schoenberg's notion of the Grundgestalt is one which has fascinated and intrigued analysts, theorists, and aestheticians alike. However, until the very end of his life, Schoenberg was reluctant to provide an absolute definition for Grundgestalt, and subsequent commentators have attempted multifarious deployments of the term, with various degrees of success. This thesis attempts a new examination and definition of the Grundgestalt, based upon a reconciliation of Schoenberg's writings with modern music theory. This locates the Grundgestalt as a median point between specific motivic structure of a given piece and the more generalised attributes of voice leading: providing a new and powerful method of interrogating generative structure. The thesis begins with an exploration of Schoenberg's own writings on the Grundgestalt, as well as an attempt to place Grundgestalt in his hierarchy of musical units. It will proceed to explore previous appropriations of the Grundgestalt, particularly the writings of Schoenberg's pupils. The main body of the thesis is provided by the development and implementation of a new methodology for Grundgestalt analysis in Brahms's Opp. 117, 118, and 119. The final two chapters expand the scope of the thesis from the exploration of the way in which a single construct may be of great generative importance to the structure of a single musical artifact, to the unifying links between larger musical communities: the Multi-Piece considers groups of compositions to be a single musical utterance, endowed with coherence and structural integrity. The thesis sets forward Brahms's Klavierstücke Op. 118 as a new example of the type. The final chapter explores the utility of the idea of Intertextuality, a structuralist coinage, in the broader exploration of musical identity and semantics.